2011
DOI: 10.1371/journal.ppat.1002241
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Competence Development, Horizontal Gene Transfer and Virulence in Streptococcus pneumoniae by a Modified Competence Stimulating Peptide

Abstract: Competence stimulating peptide (CSP) is a 17-amino acid peptide pheromone secreted by Streptococcus pneumoniae. Upon binding of CSP to its membrane-associated receptor kinase ComD, a cascade of signaling events is initiated, leading to activation of the competence regulon by the response regulator ComE. Genes encoding proteins that are involved in DNA uptake and transformation, as well as virulence, are upregulated. Previous studies have shown that disruption of key components in the competence regulon inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(125 citation statements)
references
References 57 publications
4
121
0
Order By: Relevance
“…These findings were confirmed by Oggioni et al, which show that administration of CSP in a mouse model of pneumonia infection increases virulence of pneumococci [13]. By using an opposite strategy, we have most recently shown that certain CSP analogs could competitively inhibit the competence regulon-dependent pneumonia [14]. Collectively, these results suggest that the competence regulon is important for lung infection.…”
Section: Competence Regulon Is Important For Pneumococcal Diseasessupporting
confidence: 84%
“…These findings were confirmed by Oggioni et al, which show that administration of CSP in a mouse model of pneumonia infection increases virulence of pneumococci [13]. By using an opposite strategy, we have most recently shown that certain CSP analogs could competitively inhibit the competence regulon-dependent pneumonia [14]. Collectively, these results suggest that the competence regulon is important for lung infection.…”
Section: Competence Regulon Is Important For Pneumococcal Diseasessupporting
confidence: 84%
“…More impressively, coinjection of the inhibitor peptide with S. pneumoniae in a mouse lung infection model led to improved mouse survival compared to a no-treatment control or to coinjection of S. pneumoniae with a noninhibitory peptide analogue. Additionally, coinjection of the inhibitor blocked the bacteria's ability to transform into an antibiotic-resistant strain within the mouse when DNA encoding antibiotic resistance was supplied simultaneously (226). These results indicate a potential to block acquisition of new genes by bacteria, provided that an inhibitor is supplied at a time when extracellular DNA is available.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 82%
“…S. pneumoniae competence is induced by the linear, 17-amino-acid competencestimulating peptide (CSP), which is recognized at the cell surface by the histidine kinase ComD (22). In studies probing critical residues of CSP, alanine substitution of the first amino acid generated a peptide (CSP-E1A) that could block the ability of the native CSP to bind and stimulate ComD signaling (226). During in vitro studies, adding CSP-E1A to cells significantly decreased virulence factor expression.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…More importantly, our data, for the first time, have uncovered that natural transformation makes a significantly biased contribution to the in vivo fitness and virulence of highly transformable pneumococcal isolates. Because the previously described importance of the competence system in pneumococcal virulence remains a mystery (8,60), this "addictive" requirement of natural transformation in the hypertransformable pneumococci has provided a new venue to decipher the mechanism(s) by which natural transformation enhances pneumococcal fitness and pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Natural transformation has also been implicated in allelic replacement or interstrain shuffling of the genes encoding immunoprotective proteins (e.g., PspA, CbpA, and PsrP), leading to antigenic variation and thereby evasion of human immunity (75). Lastly, the competence system has been indicated to be necessary for the carriage and virulence of the pneumococci (8,9,60), although the molecular basis of this requirement is unclear. On the other hand, natural transformation leads to transient growth arrest (78,79), fratricidal killing of noncompetent cells (80), and disruption of beneficial alleles (81).…”
Section: Discussionmentioning
confidence: 99%